The IARC Monographs on the carcinogenicity of crystalline silica / Le monografie IARC sulla cancerogenicità della silice cristallina - Guha, N.; Straif, K.; Benbrahim-Tallaa, L. (La Medicina del Lavoro, 2011)
SummaryBackground: Through extensive review of the published literature, two independent expert panels convened by the International Agency for Research on Cancer (IARC) Monographs Programme have classified crystalline silica as carcinogenic to humans while amorphous silica was not classifiable as to its carcinogenicity in humans. The panel remarked that crystalline silica in the form of quartz or cristobalite dust causes lung cancer in humans. Objectives: We discuss the literature and rationale used to support the IARC evaluations of silica. Methods: A critical review, with a focus on lung tumors, was conducted of the pertinent literature on the carcinogenic effects of crystalline silica in humans and experimental animals as well as supportive mechanistic evidence. Results: The strongest supportive evidence comes from pooled and meta-analyses that employed quantitative exposure assessment, focused on silicotics, accounted for potential confounding and demonstrated exposure-response trends. Consistency of the effect was observed despite some heterogeneity between individual studies.  Tumor site concordance was observed with rodents and further supported by mechanistic data. Conclusions: Several million workers worldwide are exposed to crystalline silica. Silicosis and lung cancer in these workers are completely preventable diseases. The IARC evaluations are critical to supporting public health interventions to protect persons at high-risk.